Pricing of highway infrastructure for transportation asset management. Issue 1 (15th January 2019) - Lim, Taehoon; Porras-Alvarado, Juan Diego; Zhang, Zhanmin
Abstract : Purpose: The purpose of this paper is to present a methodology for estimating the "price, " or the not-to-loss value, of individual highway assets, which reflects not only the assets' capital value but also economic productivity, by adopting a productivity-based asset valuation framework. The price tags can be used in prioritizing highway assets in support of transportation asset management processes. Design/methodology/approach: The methodology adopts the utility theory to consider multiple performance measures reflecting the economic productivity generated by the assets, as well as their capital value. Key performance measures are first selected, and their values are retrieved from highway asset management databases. Next, the utility functions representing decision makers' preferences convert the performance measures into utility values, which adjust the replacement cost (RC) of each highway asset to estimate price tags. To demonstrate its applicability, case studies were conducted for the highway networks of Texas and Washington State in the USA. Findings: The methodology yielded price tags that better reflect the importance of highways' roles in the economy in comparison to methods where only RCs are used. Furthermore, it was proven to be flexible enough to accommodate local conditions such as varying data availability. Originality/value: The research provides a practical and reasonable way to prioritize critical highway assets in purport of maintenance and rehabilitation resource allocations, based on their economic productivity as well as physical condition and historical cost information, enhancing the overall efficiency and effectiveness of highway asset management.